A CFD study on horizontal oil-water flow with high viscosity ratio. (16th January 2021) - Shi, Jing; Gourma, Mustapha; Yeung, Hoi
Highlights: Simulations of oil-water flow with viscosity ratio of O(10 3 ) in horizontal pipes. Demonstrated the capability of CFD models for complex multiphase flow patterns. Revealed the significance of wall contact angle on oil fouling capture. Presented the flow profiles of virtually developed core annular flow. Revealed the three-dimensional pressure distribution at the core-annulus interface. Abstract: A CFD study on horizontal oil-water flow with high viscosity ratio (O(10 3 )) was conducted with the VOF multiphase model in conjunction with the SST k–ω turbulence scheme. Suitable settings of the CFD models and numerical solution were highlighted. Particularly, the wall contact angle is shown to be important regarding the oil fouling phenomenon commonly seen in water-lubricated transportation of highly viscous oil. Satisfactory predictions of flow patterns were obtained. Water holdup calculations were consistent with measurements, attaining relative discrepancy within 14%. However, pressure gradients exhibited inconsistencies with relative discrepancy within 70%, for which poor prediction of oil fouling for some simulations is the main cause. Nevertheless, the CFD models provided reasonable estimate of the water lubrication degree for water-lubricated flow. Detailed flow characteristics of core annular flow (CAF) with high viscosity ratio were discussed in particular based on the 3D simulation results.